Effect of foliar applicaton of lime on rainfed upland cotton (Gossypium hirsutum) and tree cotton (G. arboreum) - SINGH, DEVENDRA (The Indian Journal of Agricultural Sciences, 2013)
A rainfed experiment was conducted during Ihe rainy seasons of 1990 and 1991 to assess the effect of lime on ’LRA 5166’ upland cotton (Gossypium hirsutum L.) and’ AKH 4’ tree cotton (G. arboreum L.). Application of lime @ 10.0 and 12.5%, after cessation of the monsoon, significantly increased the seed-cotton yield (28-54%), highest (1 250 kg/ha) being with lime 12.5%. The increase was owing to increased biomass (21 %), boll number (41 %) and boll weight (26%). It further increased the canopy albedo (reflectance) (324%), reduced the canopy temperature (9%). stress degree-day (324%) and transpiration (32%), resulting in increased biomass, relative water content and water-use efficiency. Application of lime in rainfed cotton. proved usefut in alleviating tile stress effect by reducing canopy temperature, transpiration stress degree-day alld ultimately increased the seed-cotton yield.